Duke radiology case review : imaging, differential diagnosis, and discussion - Nelson, Rendon C.; Provenzale, James M.; Vinson, Emily N. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2010)
"Residents, fellows, and practicing radiologists who are preparing for certification exams (the current ABR Part II oral, the future ABR Core and Certifying, CAQ and MOC) will find the new edition of this case-based review book an indispensable tool for success. Duke Radiology Case Review has long been considered one of the standards in board review, and is a well-known adjunct to the popular and well-attended board review course given by the prestigious Department of Radiology at Duke University. Close to 300 case presentations are structured to align with the way residents are taught to work through patient cases. Divided by body region and including chapters on interventional radiology and nuclear medicine, each case offers a clinical history, relevant images, and bulleted points describing the differential diagnosis. This is followed by the actual diagnosis and key clinical and radiologic facts about the diagnosis and suggested readings. This edition includes a new chapter on cardiac imaging"--Provided by publisher.